Unlocking Opportunities: Wielton Group’s Sales Strategy for Growth in the African Market - Furman, Nataliia (Otwieranie możliwości: strategia sprzedaży Wielton Group na rzecz wzrostu na rynku afrykańskim, 2025)
The aim of this research is to evaluate Wielton Group’s current sales strategy in the African market, analyse the factors influencing its performance, and identify opportunities for growth, market expansion, and efficiency improvement. Additionally, the study considers the company’s potential entry into the Egyptian market and explores strategies for successful expansion. As the third-largest producer and distributor of trailers, semi-trailers, and truck bodies in Europe, Wielton Group seeks to expand its presence into Africa, with a particular focus on Egypt. The research aims to conduct a detailed analysis of the factors influencing Wielton Group’s performance and sales opportunities. This includes evaluating the existing sales strategy, considering contemporary trends, and examining the potential of the Egyptian market as a sales channel for Wielton’s products, based on valuable and professional insights gathered from Wielton Group’s employees. The research was conducted using a qualitative data collection method – semi-structured interviews. In the empirical research phase, diverse perspectives shed light on the company’s activities in the African market. The strategic motivations for entering the African market, the challenges encountered, and the adaptive sales strategies were discussed. The decision-making process regarding entry into the Egyptian market was examined, highlighting optimism and flexible strategies. Based on the research findings, various managerial proposals are presented to help the company achieve sustainable and profitable growth in the African market and Egypt.
Quote as: Furman, N. (2025). Unlocking Opportunities: Wielton Group’s Sales Strategy for Growth in the African Market. In A. Witek-Crabb & J. Radomska (Eds.), New Trends in Business Management. Strategy, Branding, Teamwork (pp. 82-93). Publishing House of Wroclaw University of Economics and Business.
Keywords: sales strategy; African market; performance improvement; intercontinental expansion; strategia sprzedaży; rynek afrykański; poprawa wydajności; ekspansja miedzykontynentalna